Legal system of negotiation contract - Radha, Asst. Prof. D. Avan Abdul Aziz Radha; Ali, Ali (Sulaimani Journal for Humanities, 2025)
The practical reality in the scope of international trade transactions has produced a new type of pre-contractual agreements or contracts concluded before concluding the final contract, which were not known before in the general theory of contracts, and do not fall under the names and titles of contracts that the legislator addressed by definition and explanation. The negotiation contract is one of these agreements that take place in the stage preceding the contract, which has a vital and necessary role in organizing the procedural and substantive process of negotiating the conclusion of the final contract from the moment the negotiations begin until the moment they end, as a stage that reconciles the conflicting opinions of the negotiators to discuss its conditions with the aim of reaching a conclusion. Final contract.
Keywords: Precontractual agreements; Negotiation contracts; International trade transactions